Uji Sitotoksik Ekstrak Curcumin Pada Kultur Sel Limfosit T Penderita Systemic Lupus Erythematosus (SLE) - Mustikasari, Hanif; Febrinasari, Ratih Puspita; Widardo, . (Nexus Biomedika, 2013)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease that causes chronic inflammation in multiorgan, in which its etiology and pathogenesis are unclear. Curcumin has been found to have a selective cytotoxic effects on various types of cancer cells through induction of apoptosis on the various pathways. This study aimed to demonstrate whether curcumin extract had cytotoxic effects on T lymphocytes autoreactivity of patients with SLE. Methods: This research was an experimental laboratory with post test only controlled group design. Samples were using cell cultures of T lymphocytes from the veins blood of a patient with SLE and normal people. Each of T lymphocytes cell culture consisted of media control (KM), cells control (KS), the positive control with cyclophosphamide (KP1), and a group treated with curcumin extract (KP2). Curcumin extracts and cyclophosphamide were divided into 8 serial doses (50 µg/mL, 25 µg/mL, 12.5 µg/mL, 6.25 µg/mL, 3.125 µg/mL, 1.5625 µg/mL, 0.78125 µg/mL, 0.390625 µg/mL). Cell inhibition was calculated based on a percentage (%) of cell viability. Then, the data was analyzed using probit analysis to determine the dose of IC50 with SPSS for Window Release 17.0. Results: The result of cell inhibition probit analysis (IC50) on T lymphocytes cell culture of patients with SLE using curcumin extract was active (score 3) and T lymphocytes cell culture of patients with SLE using cyclophosphamide was moderately active (score 2).While, T lymphocytes cell culture of normal people using curcumin extract was active (score 3) and T lymphocytes cell culture of normal people using cyclophosphamide was moderately active (score 2). Conclusions: Curcumin extract had cytotoxic effect on T lymphocytes cell culture of SLE. The cytotoxic effect of curcumin extract on T lymphocytes cell culture of patients with SLE was stronger than cyclophosphamide. Keywords: curcumin extract, cytotoxic, SLE